Bipolarite Subjectif / Objectif et Individuel / Collectif : Le Cas de L’identite Religieuse des Jeunes Marocain - Ababou, Mohammed (جامعة سيدى محمد بن عبدالله - كلية الآداب والعلوم الإنسانية, 2008)
Individual vs. /collective, public vs. /privet and subjective vs./objective bipolarity are still the predominant bipolarities in sociology of religion and particularly in sociology of Islam. Our different inquires of beliefs and religious practices in Morocco and France show that the tensions between theses poles are more acute in Islam than others Europeans religions. As far as the first bipolarities are concerned, Islam is considered as din wa dunya, din wa dawla (“religion on world”, “religion and state ”). This conception is not only a theological abstraction: it has also practical effects on the beings of large numbers of Muslims. In fact, due to the secularisation and globalization processes of modernity this question concerns the Islamic elite Muslim as well as the simple believer. The subjective / objective bipolarity allows recognizing differences and distortions between subjective and objective identity as well as between religious belonging and religious practice. Such distinctions and distortions may be characteristic for an individual sense of Islamic identity.
Keywords: الشباب -- التدين -- المغرب